Examining the relationship between job characteristics and work engagement in mission-oriented and non-mission-oriented roles within the public sector - Ubachukwu, Udochukwu Goldia (Cranfield University, 2025)
In recent years, there has been growing academic interest in understanding how contextual features shape employee work engagement, particularly within the public sector where job roles and motivations are highly heterogeneous. While substantial literature has explored engagement through the Job Demands-Resources (JDR) theory, the influence of contextual variation across occupational roles remains under-theorised. This thesis focuses on the heterogeneity of public sector work and examines how differences between mission-oriented and non-mission-oriented roles influence the relationship between job characteristics and employee engagement. Building on longstanding criticisms that engagement research has often neglected context or reduced it to a statistical control, this study draws on Johns’ (2006) framework to conceptualise context as an integral theoretical element. The research empirically investigates how contextual variation interacts with job demands and resources to shape engagement and exhaustion. Using data from the 2021 European Working Conditions Telephone Survey (EWCTS), this study applies Multigroup Structural Equation Modelling (MG-SEM) and Moderated Structural Equation Modelling (MSEM) to a stratified sample of public sector employees across Europe. The analysis tests the differential salience of job characteristics and the buffering role of resources in mitigating the negative effects of job demands. This study finds that employees in mission-oriented public sector roles experience both higher work engagement and higher exhaustion than their non-mission-oriented counterparts, showing the importance of context in shaping psychological experiences at work. Emotional demands function as challenge demand but primarily as hindrance demands in mission roles, being strongly associated with exhaustion but not significantly with engagement. Contrary to expectations, work intensity and work-life interference showed similar effects across both role types. Among job resources, social support had greater significance for engagement in mission-oriented roles, while autonomy and voice were beneficial across roles. Only autonomy demonstrated a significant buffering effect, mitigating the impact of work intensity on exhaustion, but only in mission-oriented roles. Theoretically, the study advances JDR theory by integrating role context as a central explanatory mechanism, using Johns’ (2006) contextual framework. It challenges assumptions of motivational homogeneity in public sector work and illustrates that the effect of job demands and resources is contingent on role type. Methodologically, it employs Multigroup Structural Equation Modelling (MG-SEM) to test the moderating role of context, positioning it as a central variable rather than a control variable. Practically, the study provides a foundation for more tailored, role-sensitive engagement strategies in public sector human resource management.
Kelliher, Clare - Associate Supervisor
Keywords: Work engagement; mission-oriented roles; non-mission-oriented roles; contextual framework; heterogeneity; public sector; job demands and resources theory